THE EFFECT OF SERVICE QUALITY, TRUST AND COMPLAINT HANDLING ON CUSTOMER LOYALTY OF CUSTOMERS OF BANK JATIM NGANJUK BRANCH - nur, elvi; Dodi Kusuma Hadi Soedjoko (Proceeding Kilisuci International Conference on Economic & Business, 2025)
The aim of this study is to measure and analyze whether there is an influence of service quality, trust and complaint handling partially and simultaneously on customer loyalty of Bank Jatim Nganjuk Branch customers. The approach used in this study is quantitative and uses purposive sampling technique. The population taken is customers of Bank Jatim Nganjuk Branch and the sample used in this study is 40. The data analysis technique of this study uses multiple linear tests and uses the SPSSv23 tool. The findings of this study state that the Service Quality variable does not have a partial effect on Customer Loyalty. While Trust and Complaint handling have a partial effect on Customer Loyalty. But the three variables have a simultaneous effect on Customer Loyalty . This study provides insight and understanding of the factors that influence customer loyalty in the banking industry. By analyzing the three factors simultaneously, this study provides a new perspective on the contribution of the three variables to customer loyalty. This research provides practical implications for Bank Jatim, Nganjuk Branch. The limitation of this research is that it only discusses service quality, trust, and complaint handling as independent variables, while customer loyalty is the dependent variable.